Corneal Sequestration in a Cat - Treatment with Superficial Lamellar Keratectomy and Third Eyelid Flap Combined with Therapeutic Approach - Gomes Stuani, Deborah Cristina; Lídia da Paz Palácio,; Cortez Passos, Luana; Cortez Passos , Lara; Bezerra de Morais, Nina; Félix Xavier Júnior, Francisco Antônio; Cunha Ferreira, Tiago; Noberto de Araújo Júnior, Hélio (Acta Scientiae Veterinariae, 2025)
Background: Corneal sequestrum is a common ophthalmic condition in cats, particularly in brachycephalic breeds, whose anatomical features, such as exophthalmos and increased corneal exposure, predispose them to ocular disorders. This condition is characterized by a darkened plaque in the central or paracentral region of the cornea, affecting both the epithelium and stroma, and may progress to deeper layers, leading to corneal necrosis and risk of ocular perforation. Although its etiology remains uncertain, chronic trauma, viral infections, recurrent keratitis, and tear film abnormalities are frequently associated. Given this context, the present report aims to describe the clinical and surgical management of a corneal sequestrum case in a Brazilian Shorthair cat, treated through superficial lamellar keratectomy associated with a third eyelid flap and medical support, with emphasis on therapeutic efficacy and patient recovery. Case: A 10-year-old, neutered male Brazilian Shorthair cat, weighing 5.2 kg, was presented to a private veterinary clinic with a complaint of a dark spot in the left cornea, reported by the owner to have been present for approximately 2 months with progressive enlargement. Ophthalmic examination revealed a paracentral amber-colored lesion, typical of corneal sequestrum, without additional ocular clinical signs such as pain, blepharospasm, or epiphora. Initial management included topical treatment with lubricating, antibiotic, and anti-inflammatory eye drops. Following complementary exams and systemic stability assessment, the patient underwent a superficial lamellar keratectomy, followed by placement of a third eyelid flap, aiming to provide mechanical protection to the cornea and promote epithelial regeneration. Postoperative care maintained topical therapy, with the addition of oral dipyrone for analgesia and use of an Elizabethan collar. Seven days after surgery, complete healing of the surgical wound was observed, with no signs of pain, inflammation, or other ocular complications. Follow-up over 6 months showed no recurrence of the condition, confirming the treatment's effectiveness. Discussion: Although corneal sequestrum is more prevalent in brachycephalic breeds, it can also affect cats of other breeds, as demonstrated in this case involving a Brazilian Shorthair. The unilateral presentation, absence of additional clinical signs, and the lighter amber color of the lesion suggested a less aggressive form of the disease, allowing for favorable surgical planning and prognosis. Superficial lamellar keratectomy is considered the treatment of choice in advanced cases, as it enables effective removal of necrotic tissue, reduces recurrence rates, and facilitates faster functional recovery of the cornea. The association with a third eyelid flap, though subject to debate due to challenges in monitoring healing and applying topical medications, has shown benefits in providing physical protection to the cornea, stabilizing the tear film, and reducing exposure to irritants. The satisfactory clinical outcome in this case reinforces the applicability of this combined approach in managing corneal sequestrum in cats, even in breeds with lower predisposition. This case report contributes to the expanding body of clinical and therapeutic knowledge on the condition, emphasizing the importance of early intervention, appropriate surgical planning, and close postoperative follow-up in preserving ocular health in small animals. Keywords: necrotizing keratitis, cornea, third eyelid flap, veterinary ophthalmology.